Results from the Bottom Trawl Survey on Flemish Cap of July 1999 - Vázquez, Antonio (Northwest Atlantic Fisheries Organization, 2000)
50 páginas, 8 figuras, 35 tablas.-- Scientific Council Meeting A stratified random bottom trawl survey on Flemish Cap was carried out on July 1999 up to a depth of 730 metres. Survey results are presented and compared with results of previous surveys in the series since 1988. Abundance at age indices are presented for cod, American plaice, redfish and Greenland halibut. Results from a comparative trial between the survey gear (Lofoten) and a Campelen 1800 shrimp trawl are presented. This study was supported by the European Commission (DG XIV, Study 98-048), CSIC, IEO, IPIMAR and the Basque Government. Peer reviewed